Prophetic Ethics and Economic Self-Reliance: A Hadith-Based Model of Empowerment - Athoillah, Mohamad Anton (Islamicate Institute, 2023)
This article examines the conceptual and ethical dimensions of empowerment based on a Hadith that elevates honest labor over dependency. The selected Hadith encourages individuals to earn a living—even by collecting and selling firewood—rather than relying on others, highlighting a profound principle of ikhtiy?r (self-reliance) within Islamic ethics. The study aims to construct a theoretical framework of empowerment rooted in Prophetic teachings, emphasizing moral integrity, spiritual accountability, and economic self-sufficiency. Using a conceptual and document-based methodology, this research analyzes classical Islamic texts alongside modern scholarly literature to extract themes such as kar?mah (dignity), tamk?n (empowerment), and ‘ib?dah (labor as worship). The findings reveal that the Hadith advocates for a holistic form of empowerment that integrates individual agency with communal responsibility. It critiques both materialist and paternalist models, offering a value-based alternative that remains relevant in contemporary socio-economic discourse. This study contributes to Islamic economic thought by demonstrating how Hadith can inform ethical development strategies and foster morally grounded, resilient communities.